Risk and protective factors for depressive symptoms and suicidal behavior in the general population - Giovanna Vallim Jorgetto; João Fernando Marcolan
ABSTRACT Objective: To analyze the participants' perception of risk and protective factors for depressive symptoms and their relationship with suicidal behavior in a general adult population. Method: Exploratory-descriptive, qualitative research, using Content Analysis. Interviews with 200 participants over 18 years old, domiciled in Poços de Caldas/MG, between January 2017 and October 2018. Results: Risk factors were sadness, loneliness, problematic family relationships, losses/difficulties in emotional relationships, unemployment/financial difficulties, depressive symptoms, worsening of the feeling of depression, inability to frustration, problems in experiencing spirituality. Protective factors were family, emotional relationships, and spirituality. Suicidal behavior was related to the severity of depression, feelings of hopelessness, psychiatric comorbidities, and unemployment. Final considerations: Perception of risk factors was linked to family problems, sadness, loss of emotional relationships, unemployment, loneliness, and inability to experience frustrations; and the protective ones perceived were family and spirituality. There was a relationship between depressive symptoms and suicidal behavior.